Sikap Moderat Pengamalan Ajaran Agama Menumbuhkan Moderasi Beragama Sikap Tolerasi Dan Kecintaan Terhadap Kehidupan Bernegara - Suaidi Suaidi (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The realization of religious moderation in a multi-cultural society is a must, with religious moderation, peace can be realized mutual respect, respect and tolerance as a foundation for developing social life in society. With religious moderation, peaceful life goes well among people of different faiths. Religious moderation guides the right religious way for believers. Every religion teaches compassion and peace, so why look at others with hatred. In order to realize interaction with the foundation of religious moderation, a massive movement is needed, one of which is through learning at educational institutions. Research aims to contribute to the growth of harmony among human beings a necessity, because every religion teaches goodness. Religion is not used as a tool to justify behaviour that actually causes unrest and conflict.